PENGARUH MODEL WORD SQUARE DISERTAI MEDIA FLIPBOOK TERHADAP HASIL BELAJAR SISWA PADA SUBMATERI BRYOPHYTA SMA - Yunita, Andini Rika; Ningsih, Kurnia; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
This research aim to determine the effects of word square model with flipbook media on student learning outcomes in the sub material of moss (Bryophyte) in the Tenth Grade of SMAN 1 Pontianak. The form of research is a quasi-experimental design with a non-equivalent control group design. The samples in this research was the Tenth Grade of MIPA 2 as the experimental class an the Tenth Grade of MIPA 1 as the control class. The instrument used was in the form of multiple choice test with 20 questions. The average student learning outcomes in the experimental class was 17.09 while the average student learning outcomes in the control class was 12.88. based on the analysis of U-Mann-Whitney test with Î± = 5% Zcount< Ztable (-5.37<-1.96) which indicated that there was a difference between learning outcomes of students who were taught using a word square model with flipbook media compared to those taught using conventional learning model (discovery learning). The Effect Size value obtained was 1.47 with a hight category and contributed to 42.92% which means that the word square model with flipbook media had an effect on the student learning outcomes. Keywords: Effect, Word Square Model, Flipbook Media, Bryophyte